The Civil Code / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Law No. 131/1948 Promulgating The Civil Code. Prefatory Part: General provisions - Chapter: 1 the law and its application. - Chapter: 2 Persons. - Chapter: 3 Partition of objects and property. Section – 1 Personal Obligations Or Rights - Book 1 Obligations In General Part-I: Sources of obligation. - Chapter: 1 Contract. - Chapter: 2 Individual will. - Chapter: 3 Illicit act. - Chapter: 4 Gain without legal cause. - Chapter: 5 the law. -- Part - II: Obligation effects. Chapter: 1 Specific performance. - Chapter: 2 Execution through compensation. Chapter: 3 Implementation and guarantee methods securing the rights of creditors. -- Part - III: Factors modifying the effect of obligation. - Chapter: 1 Condition and term. - Chapter: 2 Plurality of the object of obligation. - Chapter: 3 Multiplicity of the two parties to the obligation. - Part - IV: Transfer of obligation. - Chapter: 1 Transfer of right. - Chapter: 2 Transfer of debt. Part - V: Termination of the obligation. - Chapter: 1 Settlement. - Chapter: 2 Termination of the obligation by valuable Consideration. - Chapter: 3 Termination of obligation without its settlement. -- Part Vl: Evidence of obligation. Book- 2 Nominal Contracts -- Part I :Contracts on ownership. - Chapter :1 Sale. - Chapter 2 Barter. - Chapter:3 Donations. - Chapter :4 Company. - Chapter: 5 Loan and permanent income. - Chapter: 6 Composition. -- Part - II: Contracts on benefiting by an object. - Chapter :1 Leasing . - Chapter :2 Commodation. -- Part III: Work-related contracts. - Chapter: 1 Contracting and public utilities obligation. - Chapter: 2 Labour contract. - Chapter: 3 Agency / Proxy. - Chapter :4 Bailment. - Chapter: 5 Custody. -- Part - IV: Aleatory contracts - Chapter : 1 Gambling and wagering. - Chapter: 2 Perpetual annuity. - Chapter:3 Insurance contract. -- Part V: Warranty. - Chapter: 1 Elements of the warranty.- Chapter: 2 Effects of the warranty. Section – 2 Real Rights - Book – 3 Original Real Rights -- Part -1 : Title of property. - Chapter: 1 Title of property in general. - Chapter: 2 Causes of acquisition of ownership.-- Part - II: Rights ramified from the right of ownership - Chapter: 1 Usufruct right, right of use, and right of residence - Chapter: 2 Leaseholding right - Chapter: 3 the right of easement Book – 4 Ancillary Real Rights Or Real Guarantees -- Part-I: Mortgage - Chapter: 1 Instituting a mortgage - Chapter : 2 Effects of mortgage - Chapter : 3 Termination of mortgage. - Part-II : Lien Right. - Chapter: 1 Institution of a lien right - Chapter: 2 Effects, reduction and termination of the lien right -- Part - III : Rights stemming from the right of property. - Chapter : 1 Pawn elements. - Chapter : 2 Pawn effects. - Chapter : 3 Termination of pawn right. - Chapter : 4 Certain kinds of pawn. -- Part - IV : Lien Rights. - Chapter: 1 General provisions. - Chapter : 2 Kinds of lien rights